Efforts to Improve Student Learning Outcomes through Discussion Methods in Islamic Education Learning at SMP Negeri 2 Lembah Seulawah - Muliana; Masni (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to explore the effectiveness of active learning strategies in improving student learning outcomes in Islamic Education at SMP Negeri 2 Lembah Seulawah. The research focuses on the application of methods such as cooperative learning, group discussions, and multimedia tools, which are designed to engage students more actively in the learning process. The study examines the impact of these strategies on student engagement, comprehension, and academic performance in the context of Islamic Education. The results indicate that active learning strategies significantly enhance student participation and understanding of the subject matter. Students demonstrated improved academic performance, as evidenced by an increase in post-test scores compared to pre-test scores. The use of multimedia tools and group activities fostered a more interactive and engaging classroom environment, which helped students connect better with the content and apply Islamic teachings to real-life situations. This research highlights the importance of incorporating active learning methods into Islamic Education to create a more engaging, student-centered learning environment. It also emphasizes the need for teacher training and proper planning to overcome challenges such as time management and adapting to new teaching methods. The findings suggest that active learning is a promising approach to improving student outcomes in Islamic Education, and its implementation can lead to more motivated and successful learners.